Analisis Dampak Likuiditas, Leverage dan Ukuran Perusahaan Terhadap Peringkat Obligasi - Hafizhoh Kaltsum; Dahlia Tri Anggraini (Universitas Muhammadiyah Jakarta, 2021)
The aim of this reseach is to analyze the effect of liquidity, leverage, and company size on bond rating which rated by PT. Pemeringkat Efek Indonesia (PEFINDO). The samples were processed by selecting the population with specific criteria (purposive sampling technique), 55 samples obtained from financial statement of financial companies (financing subsector) in www.idx.co.id for the 2014-2018 periods. The quntitative associative method with multiple linear regression analysis as a data analysis technique. The results of this research indicate that both liquidity and leverage have significant negative effect on bond rating partially.Company size has no significant effect on bond rating partially